2016
DOI: 10.1061/(asce)ee.1943-7870.0001141
|View full text |Cite
|
Sign up to set email alerts
|

Reflection on Molecular Approaches Influencing State-of-the-Art Bioremediation Design: Culturing to Microbial Community Fingerprinting to Omics

Abstract: Bioremediation is generally viewed as a cost effective and sustainable technology because it relies on microbes to transform pollutants into benign compounds. Advances in molecular biological analyses allow unprecedented microbial detection and are increasingly incorporated into bioremediation. Throughout history, state-of-the-art techniques have informed bioremediation strategies. However, the insights those techniques provided were not as in depth as those provided by recently developed omics tools. Advances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 111 publications
0
12
0
Order By: Relevance
“…The unprecedented advances in these areas represent a valuable source of information that is increasingly being incorporated into the improvement of bioprocesses and environmental engineering applications (e.g. wastewater treatment, bioremediation) to achieve a more sustainable environment (Czaplicki and Gunsch, 2016;Techtmann and Hazen, 2016). compilation of the application of HTS technologies to microbial water quality assessment.…”
Section: Application Of High-throughput Molecular Microbiological Toolsmentioning
confidence: 99%
“…The unprecedented advances in these areas represent a valuable source of information that is increasingly being incorporated into the improvement of bioprocesses and environmental engineering applications (e.g. wastewater treatment, bioremediation) to achieve a more sustainable environment (Czaplicki and Gunsch, 2016;Techtmann and Hazen, 2016). compilation of the application of HTS technologies to microbial water quality assessment.…”
Section: Application Of High-throughput Molecular Microbiological Toolsmentioning
confidence: 99%
“…Similar studies were carried out by Joshi et al ( 2014 ) that investigated the metagenomes isolated from petroleum muck, which revealed the indigenous microbial communities inhabiting the petroleum-contaminated sites. Recently, a number of research papers (George et al, 2011 ; Kumavath and Deverapalli, 2013 ; Bell et al, 2014 ; Pushpanathan et al, 2014 ; Ufarté et al, 2015 ; Czaplicki and Gunsch, 2016 ; Chistoserdova, 2017 ) have been published wherein different authors have emphasized individual genomic or transcriptomic approaches in bioremediation of environment. Previously researchers has largely focused on the environmental remediation using single omics-approach, however the present review specifically addresses the integrative role of the multi-omics approaches in microbial-mediated bioremediation.…”
Section: Introductionmentioning
confidence: 99%
“…Our ability to identify microbes capable of degrading contaminants or reducing their toxic effects has been boosted by the development of next generation sequencing (NGS) techniques and in silico analyses [ 176 ]. Technologies based on high-throughput analysis are very useful in shedding light on microbial community diversity, otherwise not accessible using culture dependent methods.…”
Section: Towards An Omics Bioremediation Approachmentioning
confidence: 99%